ANALYSIS ON SOCIAL LIFE IN THE NOVEL THE YEAR OF THE FLOOD BY MARGARETH ATWOOD - Montol, Sofia E.; Olii, Sanerita T.; Posumah, Jenie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to reveal the social issues in the novel The Year of The Flood. Using the descriptive and qualitative research method to gain the data which occurs in the literary work and the type of literary approaches is ‘Mimetic Theory’ by M.H Abrams in order to analyze the social aspects as the real life reflection. The main dates are mainly from the novel. The supporting data are from the reference books, journals, and articles that related to the research. The findings in the final result, there are five different aspects namely: the environments, feelings, economic factors, crime and faith which were relate and were analyzed using mimetic theory. The characters, setting, theme, and plot by Atwood are imagination of her thoughts and feelings when the novel was written. These results advance the mimetic approach can be applied to utter the social life condition in the novel appropriate with the real life condition.